Condition Monitoring of Gearbox based on Scaling Analysis of Increment Time Series - Lin Jinshan (Jixie chuandong)
Gearboxes are complex dynamics system,and the dynamics evolving process of a gearbox is hard to describe.The scaling crossover property of increment series of vibration data of gearbox is analyzed,and on this basis,an intrinsic relation between coordinates of starting and ending points of a scaling range is deduced by trigonometric function.As a result,a novel method for condition monitoring of gearboxes is developed.Moreover,the method is applied to condition monitoring of a realistic gearbox,and comparing with the conventional time domain statistical parameter method,and the effectiveness and superiority of the developed method is proved by the result.